FLUID INCLUSION STUDY IN ALPINOTYPE QUARTZ CRYSTALS FROM FISSURES IN PENTELICON MOUNTAIN - Κίλιας, Σ.; Βουδούρης, Π.; Κατερινόπουλος, Α.; Καβούρη, Σ. (Bulletin of the Geological Society of Greece, 2004)
Idiomorphic quartz crystals, up to 50 cm long, have been developed on massive, milky quartz substrate, within veins hosted by orthogneisses of the polymetamorphic system of the Pentelikon Mt. The veins fill NE-SW or/and NW-SE trending en-echelon fissures associated with the DfP deformation phase of Alpine age. Quartz-hosted fluid inclusions have been studied in order to decipher the physicochemical conditions of deposition and the relationship to the geotectonic evolution of the area. Homogenization temperatures (Th) to the liquid phase range between 175 and 240 °C clustering at 180-200 °C. Final ice melting temperatures (Tmjce) range between -0.1 and -14.5 °C corresponding to salinities between 0.2 and 23 wt% NaCI equiv. in the system HìO-NaCI. Thsalinity relationships indicate quartz crystallization under boiling conditions at temperatures 150-220 °C and pressures <1.5 Kbar. The results of this study indicate that quartz was deposited from hydrothermal fluids with a meteoric water component in the latest stages of retrograde metamorphism and regional decompressive uplift of the Pentelicon Mt metamorphic complex